Corporate social responsibility implementation on aviation company: a case study in Qatar Airways - Ida Ayu Putu Sulistya; Gede Ginaya (Politeknik Negeri Bali, 2020)
Purpose: The purpose of this research is to know the implementation of corporate social responsibility implementation in Qatar Airways and the impact of the corporate social responsibility on society and the environment.Research methods: This research uses qualitative analysis techniques to analyze the implementation of the corporate social responsibility (CSR). The data source used is secondary data and is accessed through company documents, journals, books, articles, and websites.Results and discussion: The research result of the CSR implementation in this airline is the application of triple bottom lines which is to align the economy, social, and environment but in the implementation of CSR has not given maximum attention to environmental aspects.Conclusion: Qatar Airways applies triple bottom lines, namely harmonizing the economy, social and environment, but in implementing CSR it has not given maximum attention to environmental aspects.